From Mae to Madonna : women entertainers in twentieth-century America - Sochen, June, 1937- (The University Press of Kentucky, 2008)
Entertainers were the first group of successful women to capture the public eye, taking to the stage in vaudeville and film and redefining their place in society. June Sochen introduces the white, African American, and Latina women who danced on Broadway, fell on bananas in silent films, and wisecracked in smoky clubs, as well as the modern icons of today's movies and popular music. Sochen considers such women as Mae West, Bette Davis, Shirley Temple, Lucille Ball, and Mary Tyler Moore to discover what show business did for them and what they did for the world of entertainment. She uses the li.